The Role of Emotional Intelligence and Organizational Commitment in Increasing OCB and Employee Performance (International Journal of Scientific Research and Management (IJSRM), 2019)
The need for high quality and highly contributing human resources in providing their best performance is an opportunity for organizations to achieve goals especially in the current millennial era. Employee performance can be influenced by several factors such as emotional intelligence, organizational commitment and Organizational Citizenship Behavior (OCB) which are this research variables. The purpose of this study is to determine and to analyze the influence of emotional intelligence, organizational commitment on the employee performance with Organization Citizenship Behavior (OCB) as an intervening variable at PT. Panin Dubai Syariah Bank in Surabaya area. The population in this study were all employees of PT. Panin Dubai Syariah Bank in Surabaya, Indonesia, as many as 60 employees, consisting of 40 employees of Main Branch Office of Panin Dubai Syariah Bank and 20 employees of Sub-Branch Office of Panin Dubai Syariah Bank, Ngagel Surabaya). The sampling method used is census which uses the entire population of employees of PT. Panin Dubai Syariah Bank in Surabaya. Path analysis was performed to answer research hypotheses. The results of this study are emotional intelligence and organizational commitment have a significant effect on Organizational Citizenship Behavior (OCB), emotional intelligence and organizational commitment have a significant effect on employee performance, OCB has significant effect on employee performance, and emotional intelligence and organizational commitment have a significant effect on employee performance through OCB at PT. Panin Dubai Syariah Bank in Surabaya.